PENGGUNAAN BERBAGAI KONSENTRASI EKSTRAK ETHANOL DAUN RAMBUTAN (Nephelium lappaceum L.) TERHADAP MORTALITAS LARVA Culex quinquefasciatus - Lestari, Dwi; Nuryati, Anik; Nuryani, Siti (Jurnal Teknologi Laboratorium, 2014)
Mosquitoes are insects which are responsible in transmission process of many diseases in humans and animals. One type that is often found is Culex quinquefasciatus. Culex quinquefasciatus mosquitoes serve as vectors of disease filariasis and chikungunya. the mosquito's prevention that uses synthetic insecticide affects the negative side for the environment. Natural insecticide is the safe way that can be used as insecticide.Rambutan’s leaves contain compounds of saponin and tanin, it be used for larvacide’s.This research aims to find out about ethanol extract of rambutan's leaves that can be used for larvacide, the impact, the influence of ethanol extract of rambutan's leaves towards larva mortality and the effective concentrate in the researchThis research is quasi experimental with Post Test Control Group Design. The concentrate extract of rambutan's leaves that is used is 0.025%, 0.05%, 0.1%, 0.2%, 0.4%,and 0.8% with duration 24 hours. Then, it is counted the amount of dead larvae. Then, the result is analyzed statically using Anova One Way and linear regression.The result showed that the percentage of the death of larva Culex quinquefasciatus in concentrate 0.025%, 0.05%, 0.1%,0.2%,0.4%, and 0.8% each of them are 77%,86%,87%,95%,98%,and 100%. The result of Anova One Way showed that the significant value is 0.000 (<0.05) which means that there is an impact of using rambutan's leaves extract towards larva mortality Culex quinquefasciatus.The use of Ethanol extract can cause the mortality of larva Culex quinquefasciatus.